Networks and Faces between Copenhagen and Canton, 1730-1840 - Benjamin Asmussen (Copenhagen Business School (CBS), 2018)
The overall purpose of this thesis is to understand how and why networks played a significant role for the merchants and company traders of the Danish Asiatic Company (DAC) in their trade in China. To explore this, the following research questions will be answered:  From the perspective of network analysis and prosopography, what characterised the merchants and traders as a group and how was experience transmitted among the company traders?  From the perspective of microhistory, what role did networks play for selected individual company traders? To examine these questions, an analysis on several levels is performed, starting from a broad perspective of the company, its function, and purpose from a network perspective. The rise and fall of the DAC serves as an important backdrop for the research questions. Then the focus narrows down to the societal group of merchants who were responsible for managing the company as directors and others that handled the trade with China. After examining the group as a whole using the prosopographical approach, the focus becomes narrower, turning to microhistory to get as close as possible to a small set of actors, distributed over the 100-year history of the DAC. The chapters reflect this division. In chapter II, the Danish Asiatic Company is analysed, sketching its history and examining the various purposes the company served for various actors of both individual and organisational nature. In chapter III, the focus narrows to the merchants of the company, seen as a group, approached with the help of prosopography. Here, first the merchants serving as directors will be analysed and then the company traders – both viewed as a group and with the assistance of network analysis. Finally, in chapter IV the focus becomes even narrower as four actors are provided with microhistorical narratives, followed by an analysis in view of the previous chapters.
hdl:10398/9639
Keywords: 650